Los sujetos activos del derecho de participación ciudadana en las políticas públicas - Hechavarria Prade, Oscar (Universidad Nacional del Litoral, 2022)
The participation in the public politicians, in the last three decades, he/she has come winning space as a fundamental right of the citizens to intervene in the public matters. Venezuela, Ecuador and Bolivia are example of countries that have made a recognition of this right in their great text. However, the definition of its configurative elements is still a process in development. In this sense, in the relative thing to the active fellows of the right theoretical oppositions that impact in the normative environment subsist. In this context important queries arise: are regular people of the right for the simple one made of being it or is the decisive thing their condition of national of a State? The collective fellows (juridical people) are they regular of the right? Without doubts, these are polemic questions in way some resolved and that they arise of the own social dynamics the one which favorable the birth of new rights